Pengaruh Kepemilikian Manajerial, Environmental Social Governance Disclosure, Dan Struktur Modal Terhadap Kinerja Keuangan - Lee Sel Bee; Erliana Banjarnahor (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
One of the most effective ways to assess how well a business creates value for its shareholders is by examining its financial performance. Such performance is expected to be largely driven by strategic instruments, including capital structure management, managerial ownership, and transparency in environmental, social, and governance (ESG) practices. This research seeks to analyze the influence of three key factors on corporate financial performance. Adopting a quantitative research design, the study relies on secondary data derived from the annual and sustainability reports of firms listed on the Indonesia Stock Exchange. The sample covers 20 companies that were consistently classified within the SRI KEHATI Index over the 2019–2023 period, resulting in 100 firm-year observations. The empirical findings reveal that managerial ownership does not exert a statistically significant impact on financial performance. Conversely, ESG disclosure is found to have a significant positive relationship with financial performance, whereas capital structure exhibits a significant negative association. These findings suggest that strengthening ESG governance and optimizing debt utilization levels are essential steps toward promoting sustainable corporate financial health